Bispecific T‐cell engagers for cancer immunotherapy. Issue 3 (4th November 2014) - Huehls, Amelia M; Coupet, Tiffany A; Sentman, Charles L
Abstract : Bispecific T‐cell engagers (BiTEs) are a new class of immunotherapeutic molecules intended for the treatment of cancer. These molecules enhance the patient's immune response to tumors by retargeting T cells to tumor cells. BiTEs are constructed of two single‐chain variable fragments (scFv) connected in tandem by a flexible linker. One scFv binds to a T‐cell‐specific molecule, usually CD3, whereas the second scFv binds to a tumor‐associated antigen. This structure and specificity allows a BiTE to physically link a T cell to a tumor cell, ultimately stimulating T‐cell activation, tumor killing and cytokine production. BiTEs have been developed, which target several tumor‐associated antigens, for a variety of both hematological and solid tumors. Several BiTEs are currently in clinical trials for their therapeutic efficacy and safety. This review examines the salient structural and functional features of BiTEs, as well as the current state of their clinical and preclinical development.